Vaccination principles for dogs and cats in animal shelters - Galdioli, Lucas; Botteon, Karin Denise; Rocha, Yasmin da Silva Gonçalves da; Brugnerotto, Michele; Garcia, Rita de Cassia Maria (Brazilian Journal of Veterinary Research and Animal Science, 2022)
Animal shelters are places with a high risk of exposure to infectious diseases due to the high density, population dynamics of the shelter, and the stress to which dogs and cats are subjected. The immunization process through vaccines is an essential component in the prevention and health and welfare management program for these animals. This review aims to evaluate the guidelines on vaccination of dogs and cats in shelter environments, highlighting points of comparisonwith the Brazilian reality.